O OneidaFL May 2010 52 0 Jun 12, 2010 #1 Thank you in advance, I would like to know how you got the answer 3Y+8X+3=19+8X

T TKHunny Aug 2007 3,171 860 USA Jun 12, 2010 #2 Solve for Y. 3Y + 8X + 3 = 19 + 8X Subtract 3 3Y + 8X + 3 - 3 = 19 - 3 + 8X 3Y + 8X + 0 = 6 + 8X 3Y + 8X = 6 + 8X Subtract 8X 3Y + 8X - 8X = 6 + 8X - 8X 3Y + 0X = 6 + 0X 3Y = 6 Divide by 3 3Y/3 = 6/3 Y(3/3) = 6/3 Y(1) = 2 Y = 2 Done. Y-intercept is the constant term, 2 Slope is the coefficient on X, 0 What are you not seeing?

Solve for Y. 3Y + 8X + 3 = 19 + 8X Subtract 3 3Y + 8X + 3 - 3 = 19 - 3 + 8X 3Y + 8X + 0 = 6 + 8X 3Y + 8X = 6 + 8X Subtract 8X 3Y + 8X - 8X = 6 + 8X - 8X 3Y + 0X = 6 + 0X 3Y = 6 Divide by 3 3Y/3 = 6/3 Y(3/3) = 6/3 Y(1) = 2 Y = 2 Done. Y-intercept is the constant term, 2 Slope is the coefficient on X, 0 What are you not seeing?